Exploratory algorithms to devise multi-epitope subunit vaccine by examining HIV-1 envelope glycoprotein: An immunoinformatics and viroinformatics approach. - Saurav Kumar Mishra; Kanishka Sithira Senathilake; Neeraj Kumar; Chirag N Patel; Mohammad Borhan Uddin; Taha Alqahtani; Ali Alqahtani; Hanan M Alharbi; John J Georrge (PLoS ONE)
Acquired immune deficiency syndrome (AIDS), a widespread pandemic and severe health issue, is triggered by the human immunodeficiency virus (HIV); there is no specific vaccine to cure this infection, and the situation is worsening. Therefore, this research sought to develop a vaccine with multiple epitopes against this infection targeting envelope glycoprotein (vital in host-cell interaction) through the immunoinformatics and viroinformatics approach. We identified one B-cell, eight MHC-I, and four MHC-II epitopes on its immunogen-assisted screening. In addition, these putative epitopes were conjoined concurrently using a specific linker (EAAAK, KK, GPGPG), including an adjuvant and a His-Tag at the N and C terminal, respectively, to augment its immune reaction. The final constructed entity consists of 284 amino acids; immunological evaluation demonstrated that the developed vaccine possesses antigenic features with a value of 0.6222, is non-allergenic, and has prospective physiochemical characteristics. The secondary and tertiary structures were anticipated, and their quality has been evaluated. Further, docking analysis between vaccines with TLR3 shows a strong molecular interaction with a -20.0 kcal/mol binding energy, and the stability was analysed through the MD simulation (100ns). Moreover, the designed vaccine expression and immune response were analysed, and a high vaccine expression level was found (pET28a (+)) and robust immune response followed by codon adaptation index value 0.94, 58.36% GC content, and the generation of IgM +  IgG, cytokines and interleukin. Based on overall investigation, the developed vaccine stimulates a robust immune response. Nevertheless, laboratory analysis is needed to confirm the protective potency of the vaccine.